Pentingnya Dukungan Orang Tua Dalam Penguatan Literasi Berbasis Pembiasaan Bagi Siswa Sekolah Dasar: The Importance of Parental Support in Strengthening Habit-Based Literacy for Elementary School Students - Ali Rachman; Inuriya Verawati (Tunas: Jurnal Pendidikan Guru Sekolah Dasar, 2022)
Literacy is a problem in the progress of information technology today. The purpose of writing this article is to examine how the role of parents in supporting the literacy movement, especially in elementary school-aged children, is based on habituation carried out by parents at home, the writing method used is literature review. parents in encouraging children to have literacy skills, the role of parents in this case is to help their children to choose good readings that their children like, to be role models for their children in reading, writing, listening and communicating a reading so that children also like to read and are also able to communicate what he reads, accompanying children with enthusiasm and enthusiasm so that the atmosphere becomes fun, parents open a meaningful communication atmosphere for children at home in order to strengthen literacy